Gene Discovery Analysis from Mouse Embryonic Stem Cells Based on Time Course Microarray Data - Suh, Y.J. (Sookmyung Women's University, Seoul, Republic of Korea); Cho, S.A. (Sookmyung Women's University, Seoul, Republic of Korea); Shim, J.H. (Sookmyung Women's University, Seoul, Republic of Korea); Yook, Y.J. (Sookmyung Women's University, Seoul, Republic of Korea); Yoo, K.H. (Sookmyung Women's University, Seoul, Republic of Korea); Kim, J.H. (Sookmyung Women's University, Seoul, Republic of Korea); Park, E.Y. (Sookmyung Women's University, Seoul, Republic of Korea); Noh, J.Y. (Sookmyung Women's University, Seoul, Republic of Korea); Lee, S.H. (Sookmyung Women's University, Seoul, Republic of Korea); Yang, M.H. (Sookmyung Women's University, Seoul, Republic of Korea); Jeong, H.S. (Sookmyung Women's University, Seoul, Republic of Korea); Park, J.H. (Sookmyung Women's University, Seoul, Republic of Korea), E-mail: parkjh@sookmyung.ac.kr (Molecules and cells, 2008)
An embryonic stem cell is a powerful tool for investigation of early development in vitro. The study of embryonic stem cell mediated neuronal differentiation allows for improved understanding of the mechanisms involved in embryonic neuronal development. We investigated expression profile changes using time course cDNA microarray to identify clues for the signaling network of neuronal differentiation. For the short time course microarray data, pattern analysis based on the quadratic regression method is an effective approach for identification and classification of a variety of expressed genes that have biological relevance. We studied the expression patterns, at each of 5 stages, after neuronal induction at the mRNA level of embryonic stem cells using the quadratic regression method for pattern analysis. As a result, a total of 316 genes (3.1%) including 166 (1.7%) informative genes in 8 possible expression patterns were identified by pattern analysis. Among the selected genes associated with neurological system, all three genes showing linearly increasing pattern over time, and one gene showing decreasing pattern over time, were verified by RT-PCR. Therefore, an increase in gene expression over time, in a linear pattern, may be associated with embryonic development. The genes: Tcfap2c, Ttr, Wnt3a, Btg2 and Foxk1 detected by pattern analysis, and verified by RT-PCR simultaneously, may be candidate markers associated with the development of the nervous system. Our study shows that pattern analysis, using the quadratic regression method, is very useful for investigation of time course cDNA microarray data. The pattern analysis used in this study has biological significance for the study of embryonic stem cells.